Association between Oral Candida and Bacteriome in Children with Severe ECC. (December 2018) - Xiao, J.; Grier, A.; Faustoferri, R.C.; Alzoubi, S.; Gill, A.L.; Feng, C.; Liu, Y.; Quivey, R.G.; Kopycka-Kedzierawski, D.T.; Koo, H.; Gill, S.R.
Candida albicans is an opportunistic fungal organism frequently detected in the oral cavity of children with severe early childhood caries (S-ECC). Previous studies suggested the cariogenic potential of C. albicans, in vitro and in vivo, and further demonstrated its synergistic interactions with Streptococcus mutans . In combination, the 2 organisms are associated with higher caries severity in a rodent model. However, it remains unknown whether C. albicans influences the composition and diversity of the entire oral bacterial community to promote S-ECC onset. With 16s rRNA amplicon sequencing, this study analyzed the microbiota of saliva and supragingival plaque from 39 children (21 S-ECC and 18 caries-free [CF]) and 33 mothers (17 S-ECC and 16 CF). The results revealed that the presence of oral C. albicans is associated with a highly acidogenic and acid-tolerant bacterial community in S-ECC, with an increased abundance of plaque Streptococcus (particularly S. mutans ) and certain Lactobacillus/Scardovia species and salivary/plaque Veillonella and Prevotella, as well as decreased levels of salivary/plaque Actinomyces. Concurrent with this microbial community assembly, the activity of glucosyltransferases (cariogenic virulence factors secreted by S. mutans ) in plaque was significantly elevated when C. albicans was present. Moreover, the oral microbial community composition and diversity differed significantly by disease group (CF vs. S-ECC) and sample source (saliva vs. plaque). Children and mothers within the CF and S-ECC groups shared microbiota composition and diversity, suggesting a strong maternal influence on children's oral microbiota. Altogether, this study underscores the importance of C. albicans in association with the oral bacteriome in the context of S-ECC etiopathogenesis. Further longitudinal studies are warranted to examine how fungal-bacterial interactions modulate the onset and severity of S-ECC, potentially leading to novel anticaries treatments that address fungal contributions.